Antifungal effects of chitosan films incorporated with essential oils and control of fungal contamination in peanut kernels. Issue 12 (3rd October 2019) - Chein, Su Hlaing; Sadiq, Muhammad Bilal; Anal, Anil Kumar
Abstract: The study investigated the effects of chitosan (CS) combined with essential oils (EOs) in controlling the fungal contamination in peanut kernels. The antifungal activities of CS and EOs were evaluated against Aspergillus flavus and Penicillium citrinum. CS (2%, w/v in 1% v/v acetic acid) packaging films were formulated by incorporating different EOs (4%) separately, that is, thyme (TEOs), cinnamon (CEOs), and lemongrass (LEOs), respectively. CEOs showed lowest minimum inhibitory concentration (MIC) of 40 μl/ml against A. flavus and P. citrinum . CS films incorporated with CEOs showed high tensile strength and smooth morphology with less fissures in comparison to films incorporated with TEOs and LEOs. CEO‐based CS films showed complete inhibition of fungal growth at 28°C and 5°C for 24 days. The combination of CS and CEOs coating restricted the A. flavus and P. citrinum contamination to 9.8% and 13.4%, respectively, in artificially inoculated peanut kernels at 28°C for 14 days of storage. CS can be used in combination with EOs to control postharvest fungal contamination in peanuts. Practical applications: CS are well known for the formulation of food packaging films; however, antifungal activity of CS is limited. This study explains the antifungal effects of CS and EOs. The combination of CS and EO can be used to reduce the concentration of EOs as antifungal agents which otherwise might affect the organoleptic attributes of food. The CS films incorporated with EOs are possible to use for shelf life extension and prevention of postharvest fungal contamination of agriculture commodities.